An ABC Transporter Is Involved in the Silicon-Induced Formation of Casparian Bands in the Exodermis of Rice - Hinrichs, Martin; Fleck, Alexander T.; Biedermann, Eline; Ngo, Ngoc S.; Schreiber, Lukas; Schenk, Manfred K. (Frontiers in Plant Science, 2017)
Silicon (Si) promotes the formation of Casparian bands (CB) in rice and reduces radial oxygen loss (ROL). Further transcriptomic approaches revealed several candidate genes involved in the Si-induced formation of CB such as ATP binding cassette (ABC) transporter, Class III peroxidases, ligases and transferases. Investigation of these genes by means of overexpression (OE) and knockout (KO) mutants revealed the contribution of the ABC transporter (OsABCG25) to CB formation in the exodermis, which was also reflected in the expression of other OsABCG25 in the Si-promoted formation of CB genes related to the phenolpropanoid pathway, such as phenylalanine-ammonia-lyase (PAL), diacylglycerol O-acyltransferase (DGOAT) and 4-coumarate-CoA ligase (4CL). Differential CB development in mutants and Si supply also affected the barrier function of the exodermis. OE of the ABC transporter and Si supply reduced the radial oxygen loss (ROL) from roots and Fe uptake. No effect on ROL and Fe uptake could be observed for the KO mutant. The presented research confirms the impact of the OsABCG25 in the Si-promoted formation of CB and its barrier functions.